Perancangan Reaction Wheel Inverted Pendulum Sebagai Alat Peraga Sistem Kontrol Berbasis Sistem Kontrol PID - Roche Alimin; Joshua Tandio; Handry Khoswanto (Institute of Research and Community Outreach, Petra Christian University, 2020)
A control system will be easier to understand if demo devices are available that can be used as learning media. Reaction wheel inverted pendulum is an under-actuation device so that the existence of a controller is absolutely necessary. This will be very interesting if used as a teaching aid of a control system. One application of this reaction wheel inverted pendulum is for the humanoid robot balance system. In this research project the physical design of the teaching aids and the design of the controller are carried out. The design starts from designing mechanical part first, starting from the dimensions and shape of the tool to the needs of the motor. Furthermore, a controller is designed that can balance the device automatically. The controller used is based on Arduino. The test results show that the reaction wheel inverted pendulum demo device can work quite well even though there is some drawback.